The Contribution Of Fiber In Entmoli Enteral Formula As A Functional Food - Lidya Kustiningrum; Nur Rahman; Fifi Lutfiyah (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: Enteral formula is a liquid food that can be orally or parenterally. This experimental study aims to develop an enteral formula with high nutritional value and good organoleptic properties, namely Entmoli. Entmoli is an alternative enteral formula for patients who need fiber intake. It contains high fiber with exceptional functional food like Moringa leaves. Moringa leaves have high fiber and micronutrients that help the healing process of disease. Research Methods: Entmoli's nutritional value is analyzed using comparative tests and calculations with TKPI (Indonesian Food Composition Table).Research Result: Based on the proximate test, per serving (50g), Entmoli contains 149 kcal of energy, 4.9 g of protein, 1.3 g of fat, and 27.8 g of carbohydrates. In TKPI calculations, per serving of Entmoli contains 224.2 kcal of energy, 11.3 g of protein, 7 g of fat, 28.7 g of carbohydrates, and 5.9 g of fiber.Conclusion: The difference in results may be due to the loss of nutrients due to the processing of the formula. The organoleptic test results also show that Entmoli has good scores in all aspects of organoleptic properties, including taste, color, aroma, and texture.